Peran Kepemimpinan Wirausaha dan Orientasi Wirausaha Terhadap Kinerja Keuangan IKM Makanan Di Kota Kediri - Kautsar, Achmad; Kusumaningrum, Trias Madanika; Chusnaini, Azmil (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
This study aims to analyze and determine the relationship of leadership roles and entrepreneurial orientation to the performance of SMIs in the City of Kediri, where good management of SMEs can encourage SMEs to compete with other SMIs. The population of this study was all food SMIs in Kediri City, from that population, it was agreed that the judge sampling method would examine 30 SMIs in Kediri City. Data analysis techniques in this study used path analysis. The results showed that the management of SMIs is highly dependent on the role of entrepreneurial leadership, entrepreneurial orientation, and business strategy. The results of this study indicate that entrepreneurial leadership factors and leadership orientation have a significant positive effect on business performance, while business strategies have not yet influenced business strategies and cannot be a mediating factor in this study.